¿Are stse contents contained in chemistry textbooks? (2015)
This article presents the results of a research developed in the Masters in Chemistry Education at the Universidad Pedagogica Nacional de Colombia, in Bogota 2014. In this research the presence of STSE contents in five Colombian Chemistry textbooks for tenth grade was typified. Four analysis categories were defined considering whether in the teaching of Chemistry contents, “STSE grafts”, contents through STSE, pure STSE contents, or a cross-curricular approach of them were presented. This characterization shows a curriculum limited to the discipline, with some traces of STSE approach principles within the defined categories. These contents are resources that ignore aspects of S&amp,T image, such as the historicalepistemological and the social, ethical, and moral implications of Chemistry, the activities proposed may cause that teaching chemistry makes little sense for students, and do not encourage participation in decision-making.